2021
DOI: 10.1002/jmri.27631
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of a Lower‐dose Contrast‐Enhanced 4D Dynamic MR Angiography of the Lower Extremities at 3 T Using Multisegmental Time‐Resolved Maximum Intensity Projections

Abstract: Background For peripheral artery disease (PAD), MR angiography (MRA) is a well‐established diagnostic modality providing morphologic and dynamic information comparable to digital subtraction angiography (DSA). However, relatively large amounts of contrast agents are necessary to achieve this. Purpose To evaluate the diagnostic accuracy of time‐resolved 4D MR‐angiography with interleaved stochastic trajectories (TWIST‐MRA) by using maximum intensity projections (MIPs) of dynamic images acquired with reduced dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 40 publications
(94 reference statements)
0
12
1
Order By: Relevance
“…These findings are in contrast to previous studies, which reported a high image quality for a dose of 0.03 mmolGd/kg 6,7 or even lower fixed-volume GBCA doses 8,11 . There are 2 factors that may explain this: first, these studies were performed at 3 T, and second, these studies only evaluated arterial vessels.…”
Section: Discussioncontrasting
confidence: 68%
“…These findings are in contrast to previous studies, which reported a high image quality for a dose of 0.03 mmolGd/kg 6,7 or even lower fixed-volume GBCA doses 8,11 . There are 2 factors that may explain this: first, these studies were performed at 3 T, and second, these studies only evaluated arterial vessels.…”
Section: Discussioncontrasting
confidence: 68%
“…Magnetic resonance imaging (MRI) angiography (MRA) appears as an appealing alternative, either as an MRI with multi‐station contrast enhancement (CE) or as time resolution (TR) MRA. Indeed, MRA has high diagnostic accuracy and has been recently proposed as the imaging modality of choice 1–6 …”
mentioning
confidence: 99%
“…Interobserver agreement was excellent with intraclass correlation coefficient values ranging from 0.95 to 1.0 for >50% stenosis and occlusion. Image quality was good to excellent for both readers (3.41 and 3.38), with good correlation between observer ratings (Intraclass correlation coefficient [ICC] 0.71–0.81) 6 …”
mentioning
confidence: 99%
See 2 more Smart Citations